2017
DOI: 10.1111/jac.12231
|View full text |Cite
|
Sign up to set email alerts
|

Late‐season photosynthetic rate and senescence were associated with grain yield in winter wheat of diverse origins

Abstract: There is a lack of studies that have investigated grain yield, its components and photosynthesis in late stages of wheat growth, giving us insufficient understanding of how these factors interact to contribute to yield during this period. As a result, three field experiments were carried out examining 20 winter wheat genotypes of diverse origins under irrigated, terminal drought and dryland conditions in the southern Idaho. Our objective was to evaluate the interaction between post-anthesis physiological trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 43 publications
1
29
0
1
Order By: Relevance
“…The authors revealed that the photosynthesis at these stages is determined by the size of the carbon sink which is genetically predefined. The suggestion for wheat breeders was subsequently to select for higher grain number, which is likely to come along with a prolongation of the ability to fill the grains (Liang et al, 2018). But besides leaf longevity, also the photosynthetic capacity is relevant for grain yield as shown here with the results of the SPAD measurements.…”
Section: Gcd and Grain Yield: Correlation Does Not Imply Causationmentioning
confidence: 67%
See 3 more Smart Citations
“…The authors revealed that the photosynthesis at these stages is determined by the size of the carbon sink which is genetically predefined. The suggestion for wheat breeders was subsequently to select for higher grain number, which is likely to come along with a prolongation of the ability to fill the grains (Liang et al, 2018). But besides leaf longevity, also the photosynthetic capacity is relevant for grain yield as shown here with the results of the SPAD measurements.…”
Section: Gcd and Grain Yield: Correlation Does Not Imply Causationmentioning
confidence: 67%
“…Therefore, the effect of grains per spike on total grain yield was in parts mediated by the extended canopy longevity. Similarly, in the study of Liang et al, 2018, the degree of senescence during grain filling was also negatively correlated to yield but not to thousand grain weight. The authors revealed that the photosynthesis at these stages is determined by the size of the carbon sink which is genetically predefined.…”
Section: Gcd and Grain Yield: Correlation Does Not Imply Causationmentioning
confidence: 79%
See 2 more Smart Citations
“…It is proposed that a delay in flag leaf senescence greatly influences grain yield in cereal crops (Thomas and Howarth, 2000;Borrill et al, 2015). In wheat, early flag leaf senescence has been found to affect grain yield negatively (Gregersen et al, 2013) including under dryland conditions (Liang et al, 2018), while delayed flag leaf senescence is positively associated with higher grain yield (Verma et al, 2004) and harvest index (Carmo-Silva et al, 2017). Drought-tolerant varieties have a higher CO 2 uptake rate in the flag leaves which contributes to yield stability (Paul et al, 2016).…”
Section: Flag Leaf Senescencementioning
confidence: 99%